Investigation of Dielectric Properties of Polyethylene-Clay Nanocomposites for Quantifying Nanofiller Dispersion - ESMER, KADİR (POLYMER SOC KOREA, 2018)
This study examined the dielectric properties of linear low density polyethylene (LLDPE)/organo-clay nano composites including the same amount of maleic anhydride grafted polyethylene (PE-g-MA) and oxidized polyethylene (OxPE) as compatibilizer at different frequencies (10(-1)-10(+7) Hz) and temperatures (237-373 K). The dielectric constant of natural LLDPE remained constant at around 1.5, depending on the temperature rise and frequency while that of LLDPE-PE-g-MA/clay and LLDPE-OxPE/clay nanocomposites increased up to 4.8 and 2.8, respectively, linearly with increasing temperature. Especially in the low frequency region, a Maxwell-Wagner-Sillars polarization was observed in composite structures with an increase in temperature due to the dipolar effect. It has been concluded that the clay in the polymer matrix was more homogeneously dispersed than OxPE due to the compatibilizing effect of PE-g-MA and that different polarization mechanisms were at play for each compatibilizer.
Keywords: low density polyethylene; composites; nanoparticles; polymers; dielectric properties; MECHANICAL-PROPERTIES; ELECTRICAL-PROPERTIES; (LLDPE)/CLAY NANOCOMPOSITES; FILMS; POLYPROPYLENE